Capacity building for the practice of irrigated agriculture - Divine, Anisa Joy, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2000)
Irrigated agriculture is sustainable when irrigation experts join with other community members to develop and apply sound principles and practices in the common interest. Necessary and sufficient principles and practices are presented as an action map consisting of two parts: 1) nine essential processes - ecological, administrative, accounting, educational, integrative, scientific, marketing, entrepreneurial, and service processes; and 2) a development spiral that, when institutionalized, matures into an achievement cycle. When these tools are applied according to a proven protocol, significant and sustainable success has been achieved. The action map and protocol are described in this paper. The map is based experiences in sustained agricultural and industrial development over the last 150 years in Denmark, the USA, Greece, Guatemala, and elsewhere. The map and protocol allow the user to integrate the principles and practices into a blueprint that provides a framework for the diagnostic analysis and program design needed to develop successful, sustainable irrigated agricultural systems.
Irrigation and drainage in the new millennium
Not digitized by CSUL Digital Services.
Presented at the 2000 USCID international conference, Challenges facing irrigation and drainage in the new millennium on June 20-24 in Fort Collins, Colorado.